Protective role of supplemental vitamin E and selenium on lipid peroxidation, vitamin E, vitamin A, and some mineral concentrations of Japanese quails reared under heat stress - Şahin, Kazım; Şahin, Nurhan; Yaralioglu, S; Onderci, M (Springernature, 2002)
This study was conducted to determine the effects of vitamin E and selenium (Se) on lipid peroxidation (MDA), serum and liver concentration of antioxidant vitamins, and some minerals of Japanese quails reared under heat stress (34degreesC). One hundred twenty 10-d-old Japanese qualis (60 males, 60 females) were randomly assigned to 4 treatment groups, 3 replicates of 10 birds each. The experiment was designed in a 2x2 factorial arrangement using two levels of vitamin E (125 and 250 mg/kg of diet) and two levels of selenium (0.1 and 0.2 mg/kg of diet). Greater dietary vitamin E and selenium inclusions resulted in a greater (p = 0.001) serum vitamin E and vitamin A, but lower (p = 0.001) MDA concentrations. Liver vitamin E and vitamin A concentrations increased (p = 0.001) and MDA concentrations decreased (p = 0.001) when both dietary vitamin E and selenium increased. No interactions between vitamin E and selenium were detected (p greater than or equal to 0.11) for any parameters. Increasing both dietary vitamin E and selenium caused an increase in serum concentrations of Fe and Zn (p = 0.001), but a decrease in serum concentration of Cu (p = 0.001). Results of the present study showed that dietary vitamin E and selenium have synergistic effects ana that supplementing a combination of dietary vitamin E (250 mg/kg of diet) and selenium (0.2 mg/kg of diet) offers a good management practice to reduce heat stress-related depression in performance of Japanese quails.
Keywords: Japanese quails; heat stress; vitamin E; selenium; MDA; Fe; Zn; Cu